Therapeutic potential of Syzygium cumini L. extract in treating anxiety in adult zebrafish (Danio rerio): Behavioral, toxicological, and molecular evidence involving the GABAergic and serotonergic pathways - Cássia Taiane Viana Moraes; Gabriel Martins de Araújo Sousa; Ariel Falanga de Oliveira; Igor de Codes Soares; Paula Ticiani Alves de Souza; Lucca Moura de Freitas; Mário Guilherme de Paula Sales; Vitória Isabele Gomes Ferreira; Paula Alexandre de Freitas; Saulo Chaves Magalhães; Katarine Ferreira da Silva; Luís Sérgio Fonteles Duarte; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Determination of soil organic carbon and nutrients by diffuse spectrorradiometry in the Cerrado Mineiro region, Brazil: evaluation of strategies for calibration of hyperspectral models - Everson Cezar; Tatiane Amancio Alberton; Evandro Freire Lemos; Nicole Ghinzelli Vedana; Karym Mayara de Oliveira; Luís Guilherme Teixeira Crusiol; Marlon Rodrigues; Renan Falcioni; Jose Alexandre Melo Demattê; Marcelo Henrique Procópio Pelegrino; Marcos Rafael Nanni (International Journal of Remote Sensing, 2026)

Relationship between season and spermatozoa traits of captive-reared agoutis from Brazilian semiarid - Maiko Roberto Tavares Dantas; Luana Grasiele Pereira Bezerra; Ana Glória Pereira; Romário Parente dos Santos; João Batista Freire Souza-Junior; Leonardo Lelis de Macedo Costa; Alexandre Rodrigues Silva (Environmental Science and Pollution Research, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Cryopreservation efficiency of red-rumped agouti (Dasyprocta leporina) sperm obtained from different origins through epididymal retrograde flushing or electroejaculation - Thibério de Sousa Castelo; Andréia Maria da Silva; Gislayne Christianne Xavier Peixoto; Ana Liza Paz Souza; Lívia Batista Campos; Gabriela Liberalino Lima; Maiko Roberto Tavares Dantas; João Batista Freire de Souza-Junior; Alexandre Rodrigues Silva (Cryobiology, 2023)

Bacterial identification in cerebrospinal fluid of domestic species with neurologic signs: a retrospective case-series study in 136 animals (2005–2021) - Márcio Garcia Ribeiro; Thiago Tourinho Pereira; Patrik Júnior de Lima Paz; Beatriz Oliveira de Almeida; Carmen S. Araújo Cerviño; Carolina Aparecida Rodrigues; Gabrielly Terra Sartori Santos; Larissa Maria de Souza Freire; Fábio Vinicius Ramos Portilho; Marcelo Fagali Árabe Filho; Natália Rodrigues Paschoal; Thaís Spessotto Bello; et al. (Brazilian Journal of Microbiology, 2023)

Correction to: Expression of O-glycosylated oncofetal fibronectin in alternatively activated human macrophages - Marcos Andre Rodrigues da Costa Santos; Jhenifer Santos dos Reis; Carlos Antonio do Nascimento Santos; Kelli Monteiro da Costa; Pedro Marçal Barcelos; Karen Queiroz de Oliveira Francisco; Pedro Antônio Guimarães Notaroberto Barbosa; Emanuelle Damasceno Souza da Silva; Celio Geraldo Freire-de-Lima; Alexandre Morrot; Debora Decote-Ricardo; Israel Diniz-Lima; et al. (Immunologic Research, 2023)

Expression of O-glycosylated oncofetal fibronectin in alternatively activated human macrophages - Marcos Andre Rodrigues da Costa Santos; Jhenifer Santos dos Reis; Carlos Antonio do Nascimento Santos; Kelli Monteiro da Costa; Pedro Marçal Barcelos; Karen Queiroz de Oliveira Francisco; Pedro Antônio Guimarães Notaroberto Barbosa; Emanuelle Damasceno Souza da Silva; Celio Geraldo Freire-de-Lima; Alexandre Morrot; Debora Decote-Ricardo; Israel Diniz-Lima; et al. (Immunologic Research, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Chronic exposure to lead acetate promotes changes in the alveolar bone of rats: microstructural and physical–chemical characterization - Lodinikki Lemoy Davis; Walessa Alana Bragança Aragão; Géssica de Oliveira Lopes; Luciana Guimaraes Eiró; Alexandre Rodrigues Freire; Felippe Bevilacqua Prado; Ana Cláudia Rossi; Allan da Silva Cruz; Kelly das Graças Fernandes Dantas; Alan Rodrigo Leal Albuquerque; Simone Patricia Aranha Paz; Rômulo Simões Angélica; et al. (Environmental Science and Pollution Research, 2022)

Ecological risks associated to trace metals of contaminated sediments from a densely urbanized tropical eutrophic estuary - Christiane do Nascimento Monte; Ana Paula de Castro Rodrigues; Alexandre Rafael de Freitas; Bernardo Ferreira Braz; Aline Soares Freire; Renato Campello Cordeiro; Ricardo Erthal Santelli; Wilson Thadeu Valle Machado (Environmental Monitoring and Assessment, 2021)

IgG Subclass Analysis in Patients with Chagas Disease 4 Years After Benznidazole Treatment - Maurício Llaguno; Marcos Vinícius da Silva; Fernanda Rodrigues Helmo; Lara Rocha Batista; Djalma Alexandre Alves da Silva; Rodrigo Cunha de Sousa; Luiz Antonio Pertili Rodrigues de Resende; Eliane Lages-Silva; Carlo José Freire Oliveira; Juliana Reis Machado; Denise Bertulucci Rocha Rodrigues; Dalmo Correia; et al. (Acta Parasitologica, 2021)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Purification, Biochemical Characterization, and Amino Acid Sequence of a Novel Type of Lectin from Aplysia dactylomela Eggs with Antibacterial/Antibiofilm Potential - Rômulo Farias Carneiro; Renato Cézar Farias Torres; Renata Pinheiro Chaves; Mayron Alves de Vasconcelos; Bruno Lopes de Sousa; André Castelo Rodrigues Goveia; Francisco Vassiliepe Arruda; Maria Nágila Carneiro Matos; Helena Matthews-Cascon; Valder Nogueira Freire; Edson Holanda Teixeira; Celso Shiniti Nagano; et al. (Marine Biotechnology, 2017)

Connectivity maintain mammal assemblages functional diversity within agricultural and fragmented landscapes - Marcelo Magioli; Katia Maria Paschoaletto Micchi de Ferraz; Eleonore Zulnara Freire Setz; Alexandre Reis Percequillo; Michelle Viviane de Sá Santos Rondon; Vanessa Villanova Kuhnen; Mariana Cristina da Silva Canhoto; Karen Evelyn Almeida dos Santos; Claudia Zukeran Kanda; Gabriela de Lima Fregonezi; Helena Alves do Prado; Mitra Katherina Ferreira; et al. (European Journal of Wildlife Research, 2016)